O Patrimônio imaterial e as manifestações religiosas: entre fé e caminhadas em Taquaritinga do Norte-PE. - Coelho, José Roberval (2024)
The central theme of this research is intangible heritage: religious manifestations and public policies. The general objective is to analyze the "Caminhada de Santo Amaro," its relationships and the constituents of the idea of heritage. The specific objectives are to identify public policies for the preservation of intangible heritage, understand the process of valorization and preservation of the intangible heritage of Pernambuco, and draw up a visit itinerary. The research adopts a qualitative and documentary approach because records related to the "Caminhada de Santo Amaro" are scattered and in various formats such as websites, newspapers, blogs, videos, magazines, author reports, registration forms, among others. As a result of the research, it was found that there are no municipal laws protecting the "Caminhada de Santo Amaro" as intangible heritage or as a religious manifestation. Still based on the sources consulted, the motivation of people to undertake a 180 km journey over 6 days becomes evident. The "Caminhada de Santo Amaro" has been carried out for seventeen years, starting from the Santo Amaro das Salinas church in Recife to Taquaritinga do Norte, in the Agreste region of Pernambuco. The visiting itinerary includes the trajectory of the walk, providing information about the cities visited, their traditions, and tourist attractions. QR Code barcodes in each city make it more accessible and practical to locate the municipality. By scanning the code, the reader is directed through Google Maps to the best route to reach that scanned destination. Its ultimate goal is to contribute to and publicize the memories of the "Caminhada de Santo Amaro," as well as to disseminate the cultures and traditions of the cities it passes through.